Diabetes diagnosis and care in sub-Saharan Africa: pooled analysis of individual data from 12 countries - Manne-Goehler, Jennifer; Bärnighausen, Till (The lancet. Diabetes & Endocrinology, 2016)
Despite widespread recognition that the burden of diabetes is rapidly growing in many countries in sub-Saharan Africa, nationally representative estimates of unmet need for diabetes diagnosis and care are in short supply for the region. We use national population-based survey data to quantify diabetes prevalence and met and unmet need for diabetes diagnosis and care in 12 countries in sub-Saharan Africa. We further estimate demographic and economic gradients of met need for diabetes diagnosis and care.